The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12144-018-9944-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-control and regulatory foci in money-saving behaviours among children

Abstract: The studies aimed to discover if it is possible to increase children's ability to defer consumption in favour of saving money by drawing attention to the importance of self-control and by inducing regulatory focus of promotion or prevention. The first study confirmed that economic behaviours of children are connected to their level of self-control. Next, in two experimental studies, self-control and regulatory focus were experimentally induced in 9-to 11-year-old children. The second study (n = 158) showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In previous studies conducted among children of the same age group and using similar experimental procedures (analyses of the effects of self-control and regulatory focus on children's saving behaviors), effect sizes were rather small: Crame ´r's V ranged from 0.22 to 0.23 (Trzci nska et al, 2021). Based on those studies' effect sizes, an a priori sample size calculation with G Ã Power (Faul et al, 2007) was done for the present study.…”
Section: Participantsmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous studies conducted among children of the same age group and using similar experimental procedures (analyses of the effects of self-control and regulatory focus on children's saving behaviors), effect sizes were rather small: Crame ´r's V ranged from 0.22 to 0.23 (Trzci nska et al, 2021). Based on those studies' effect sizes, an a priori sample size calculation with G Ã Power (Faul et al, 2007) was done for the present study.…”
Section: Participantsmentioning
confidence: 97%
“…For example, children who regularly receive pocket money possess better knowledge of the value of money than those who do not (Kupisiewicz, 2004); parental guidance is also crucial in learning money-saving habits (Otto, 2009;Bernheim et al, 2001). Individual characteristics may also influence children's financial behaviors, for example, high self-control (Otto, 2009(Otto, , 2013 and a promotion regulatory focus (Trzci nska et al, 2021) have been identified as important features that contribute to children saving money.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in the field of economic psychology, particularly in recent years, have looked at people's attitudes and beliefs about money. According to cross-sectional studies, there is a positive relationship between financial attitude and financial literacy (Trzcińska, Sekścińska, & Maison, 2018). As a result, we can formulate a hypothesis in the following manner.…”
Section: Financial Attitude and Fsmentioning
confidence: 98%
“…Financial experts should promote budgeting when classified to help people develop self-control in financial management decisions (Liu, Yilmazer, Loibl, & Montalto, 2019). The results of the research are particularly relevant for financial education strategists, where financial education requires not just the delivery of information on the effectiveness of specific financial conduct, but also the cognitive stimulation of individual skill concepts such as self-control amidst social interaction (Trzcińska, Sekścińska, & Maison, 2018).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%